2022
DOI: 10.1212/wnl.0000000000200173
|View full text |Cite
|
Sign up to set email alerts
|

Serious Cardiac Arrhythmias Detected by Subcutaneous Long-term Cardiac Monitors in Patients With Drug-Resistant Epilepsy

Abstract: Background:Epilepsy is associated with an increased risk of cardiovascular disease and premature mortality, including sudden unexpected death in epilepsy (SUDEP). Of concern, serious cardiac arrythmias might go undetected from routine epilepsy and cardiac investigations.Methods:This prospective cohort study aimed to detect cardiac arrhythmias in patients with chronic drug-resistant epilepsy (≥5 years duration) using subcutaneous cardiac monitors for a minimum follow-up duration of 12 months. Participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…If the incidence of serious arrhythmias is indeed as high as reported by Sivathamboo et al, 9 should we recommend long-term monitoring with IRL for all patients with drug-resistant epilepsy? It could be that early detection and treatment of serious arrhythmias may prevent premature mortality and potentially SUDEP.…”
Section: Commentarymentioning
confidence: 94%
See 1 more Smart Citation
“…If the incidence of serious arrhythmias is indeed as high as reported by Sivathamboo et al, 9 should we recommend long-term monitoring with IRL for all patients with drug-resistant epilepsy? It could be that early detection and treatment of serious arrhythmias may prevent premature mortality and potentially SUDEP.…”
Section: Commentarymentioning
confidence: 94%
“…In the current study by Sivathamboo et al 9 report on the incidence of serious cardiac arrhythmias, defined as warranting additional cardiologist assessment or intervention, in a prospective observational study of 31 adult patients with refractory epilepsy. The primary endpoint was detection of serious arrhythmias, and the secondary endpoint was the time to the first detection of a serious event.…”
Section: Commentarymentioning
confidence: 97%
“…However, a growing body of evidence suggests that damage caused by repeated seizures in uncontrolled epilepsy leads to incremental electrical and mechanical cardiac dysfunction (Tigaran et al, 2003; Verrier et al, 2020). Specifically, long‐term monitoring studies of patients with chronic epilepsy revealed a significant proportion with clinically relevant cardiac arrhythmia and T‐wave alternans, but this was not observed in newly diagnosed cases (Pang et al, 2019; Sivathamboo et al, 2022). Myocardial infarction (MI) is another serious cardiac comorbidity associated with epilepsy.…”
Section: Epilepsy and Its Comorbidities: A Role For The Adenosine Systemmentioning
confidence: 99%
“…33,35,36 In people with drug-resistant epilepsy, implantable cardiac monitors detected a high incidence of clinically significant cardiac arrhythmias. 37 Ictal and postictal arrhythmias, such as asystole and ventricular fibrillation, have been reported, some of which are associated with (near) SUDEP. [38][39][40] Although the authors discuss the temporal dissociation of cardiac and respiratory dysfunction, these events can arise concurrently as well as one without the other.…”
mentioning
confidence: 99%
“…The incidence of electrocardiographic (ECG) abnormalities is higher in intractable forms of epilepsy, surrounding seizures, and in SUDEP cases 33,35,36 . In people with drug‐resistant epilepsy, implantable cardiac monitors detected a high incidence of clinically significant cardiac arrhythmias 37 . Ictal and postictal arrhythmias, such as asystole and ventricular fibrillation, have been reported, some of which are associated with (near) SUDEP 38–40 .…”
mentioning
confidence: 99%